Role of Arabian Sea warming on the Indian summer monsoon rainfall in a regional climate model. (18th October 2019) - Mishra, Alok K.; Dwivedi, Suneet; Das, Sushant
Abstract: The role of the Arabian Sea (AS) warming on the Indian summer monsoon rainfall is investigated using regional climate model‐Regional Climate Model version 4.7 of International Centre for Theoretical Physics. The model realistically simulates the rainfall, temperature, low‐level winds and vertically integrated moisture flux over the Indian region during the years 2006–2015. It is found that the AS warming decreases the rainfall over most parts of the India, which is mainly due to decrease in the convective precipitation over these regions. The AS warming reduces the magnitude of westerly winds in the southern Bay of Bengal and AS; enhances the moisture convergence over the AS; and causes the prohibition of the moisture‐laden winds from the AS to reach to the Indian land regions resulting into decreased precipitation. The effect of anti‐cyclonic circulation produced over the central India as a result of the AS warming is to further reduce the monsoon rainfall. It is also shown that the AS warming increases the extreme rainfall over most parts of India. Abstract : The role of the Arabian Sea (AS) warming on the Indian summer monsoon rainfall (ISMR) is investigated using a regional climate model. The AS warming decreases the ISMR, which is mainly due to decrease in convective precipitation. The AS warming reduces magnitude of westerly winds, enhances moisture convergence over the AS; and causes prohibition of moisture‐laden winds from the AS resulting into decreased ISMR. The AS warming increases extreme rainfall over most parts of India.